Transcatheter Therapy for Coarctation of Aorta: Analysis of 150 Cases (Cardiovascular Journal, 2017)
Background: This study was conducted to analyze the outcome of transcatheter intervention of Coarctation of aorta carried out on 150 patients.Methods: This was a retrospective study, conducted in Pediatric Cardiology Unit, Combined Military Hospital Dhaka and Lab Aid Cardiac hospital from January 2007 to December 2015. Data were collected by chart review.Results: Age of the patient varies from 7 days to 28 years. Sixty six (44%) patients were female and rest were male. Native coarctation was 138 (92%) and post surgical re-coarctation was 12 (8%). Neonatal critical Coarctation was 60 (40%). Thirty six (24%) cases were detected when they were investigated for hypertension. Abdominal coarctation was found in 18 cases (12%). Multiple coarctation was found in 9 (6%) cases. Six cases (4%) had balloon angioplasty twice and 12(8%) cases had stenting after recoarctation as they had body weight above 15 kg. Aneurysm and aortic dissection was observed in one (0.66%) case. Thrombophlebitis observed in 3(2%) cases and temporary pulse loss in 9 (6%) cases. No mortality was noticed.Conclusion: Balloon angioplasty for coarctation of aorta and stenting in suitable cases is a safe and effective measure to treat coarctation of aorta.Cardiovasc. j. 2017; 10(1): 56-62